Eikenella corrodens: Pathogenesis and clinic aspects. (Colombia Medica, 2006)
The oral microbiological environment is unique and has a complex dynamic. It has been estimated that about 500 species of bacteria inhabit the human oral cavity and about 22 genera of them are the most dominant. The most frequently isolated from infected pockets of the oral cavity bacteria which are also potential pathogens form a small group of gramnegative microorganisms among which are included the following: Actinobacillus actinomycetemcomitans, Bacteroides forsythus, Campylobacter spp., Capnocytophoga spp., Eikenella corrodens, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, and Streptococcus milleri-group. E. corrodens is distinguished for being an opportunistic oral pathogen. It can also produce extra-oral infections acting either as an infectious agent itself or together with other bacteria. Referring to E. corrodens the present review will not only demonstrate different aspects about microbiological and biochemical characteristics, but also the actual knowledge on pathogenesis mechanism, like polysaccharides, outer membrane protein, lectin-like adhesin complex, pili, and other mechanisms will be systematized and discussed. Oral and extra-oral infections and other risking factors like endocarditis; osteomyelitis, intra-abdominal infections, their diagnosis and antimicrobial agents will be also considered in this paper.